UKRAINE AS A WEAK STATE: INSTITUTIONAL DIMENSION - Зарембо, К.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The application of the analytical category of a „weak state’’ in Ukraine’s security studies is proposed. In particular, the article lists the most wide-spread causes of a state’s weakness. Hence, the author argues the applicability of this analytical category towards the Ukrainian case, using one of the three empirical indicators – the institutional capacity of the Ukrainian state. Finally, directions for further related research are suggested.